2010
DOI: 10.17221/10/2010-pse
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and vertical distribution and pollution assessment of soil fluorine in a lead-zinc mining area in the Karst region of Guangxi, China

Abstract: Soil pollution of fluorine is a serious environmental problem in the world, and the fluorine pollution evaluation of spatial and vertical distribution study in the Karst region is quite limited. In this study, the farmland around lead-zinc mine in the Karst region was chosen as the study area. Ninety-one upper layer soil samples and two soil profiles (one in paddy field, the other one in aerated field) samples were taken. The average concentration of total fluorine of topsoil in the paddy fields is 378 mg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…Except the value reported by US NAS [25], Washington DC, America and Smith and Hodge [26], fluoride in American soil is lower than this study, while others such as Toma et al [27], Moldova; Shomar et al [28], Israel; Zhang et al [29], China and others have comparable value of total fluoride with this study. The water soluble content of soil in this study is a bit higher than that of reported in literature, but comparable values also reported in America [25] and New Zealand [30].…”
Section: Comparison Of Fluoride Levels In This Study With Literature contrasting
confidence: 60%
“…Except the value reported by US NAS [25], Washington DC, America and Smith and Hodge [26], fluoride in American soil is lower than this study, while others such as Toma et al [27], Moldova; Shomar et al [28], Israel; Zhang et al [29], China and others have comparable value of total fluoride with this study. The water soluble content of soil in this study is a bit higher than that of reported in literature, but comparable values also reported in America [25] and New Zealand [30].…”
Section: Comparison Of Fluoride Levels In This Study With Literature contrasting
confidence: 60%
“…Spectrometric determinations seem to be rather uncommon . Ion chromatography and potentiometry are predominantly used (e.g .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the natural enrichment of uorine in soils and rocks, more than a thousand mg/kg of uorine in the soil is frequently observed in construction sites in South Korea. The high contents of uorine in the soil can also arise from various types of human activities, such as coal combustion, mineral processing of uorine-containing minerals, smelting of non-ferrous metals like aluminum, land lling of phosphate-gypsum wastes, and the application of sludge and phosphate fertilizers (Arnesen et al, 1995;Gilpin and Johnson, 1980;Xie et al, 2001;Loganathan et al, 2006;Zhang et al, 2010;Mikkonen et al, 2018;Fuge, 2019;Wang et al, 2021). The stabilization of uorine-contaminated soils is considered necessary to prevent the adverse effects of uorine-enrichment in the soil.…”
Section: Introductionmentioning
confidence: 99%